2016
DOI: 10.1371/journal.pone.0164550
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxyvitamin D and TSH as Risk Factors or Prognostic Markers in Thyroid Carcinoma

Abstract: ObjectiveThe increasing incidence of thyroid nodules demands identification of risk factors for malignant disease. Several studies suggested the association of higher TSH levels with cancer, but influence of 25-hydroxyvitamin D (25OHD) is controversial. This study aimed to identify the relationship of thyroid cancer with higher TSH levels and hypovitaminosis D and to evaluate their influence on prognostic characteristics of papillary thyroid carcinomas (PTC).MethodsWe retrospectively evaluated 433 patients sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
3
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 61 publications
1
23
3
1
Order By: Relevance
“…Penna-Martinez et al, (2012), reported an association between the incidence of differentiated thyroid cancer (DTC) and low levels of 25(OH)D and 1,25(OH)2D in certain CYP24A1 haplotypes. On contrary, other studies reported no significant association between serum level of 25(OH) D and thyroid cancer risk (Jonklaas et al, 2013;Ahn et al, 2016;Danilovic et al, 2016;Kim, 2016;Choi et al, 2017). Another marker assessed in the current study is the serum levels of PDGF-AB in the patients' groups, it revealed a significant increase in the level of PDGF-AB in the TC and BN patients compared to the control group.…”
Section: Discussioncontrasting
confidence: 81%
“…Penna-Martinez et al, (2012), reported an association between the incidence of differentiated thyroid cancer (DTC) and low levels of 25(OH)D and 1,25(OH)2D in certain CYP24A1 haplotypes. On contrary, other studies reported no significant association between serum level of 25(OH) D and thyroid cancer risk (Jonklaas et al, 2013;Ahn et al, 2016;Danilovic et al, 2016;Kim, 2016;Choi et al, 2017). Another marker assessed in the current study is the serum levels of PDGF-AB in the patients' groups, it revealed a significant increase in the level of PDGF-AB in the TC and BN patients compared to the control group.…”
Section: Discussioncontrasting
confidence: 81%
“…Danilovic et al, evaluated 433 patients that underwent thyroidectomy for thyroid nodules and observed no significant differences in preoperative 25(OH)D levels or quartile distribution between benign and malignant cases. Decreased 25(OH)D levels were not overtly associated with a poorer prognosis among 187 patients with PTC [ 71 ]. The author also investigated 410 patients that underwent ultrasonography-guided fine-needle aspiration for thyroid nodules and found that serum 25(OH)D levels and the prevalence of vitamin D insufficiency (25(OH)D level < 75 nmol/L) did not significantly differ between benign and malignant thyroid nodules.…”
Section: Vitamin D and Thyroid Cancersmentioning
confidence: 99%
“…23 Although most studies support a decrease in serum selenium levels in patients with thyroid cancer, and supplementation with selenium may reduce the risk of certain diseases, the decline is not specific, except for thyroid cancer, including infections, many diseases, including Parkinson's, can cause selenium levels to decline. 24 The significance of vitamin D in the diagnosis and prognosis of thyroid cancer is also conflicted, although in 2016 and 2017, Choi 25 and Danilovic 26 denied serum 25 (OH) D 3 's role in determining the risk of thyroid cancer in their studies respectively. But in 2018, Zhang et al found that the content of 1,25 (OH) 2 D 3 in the serum of patients with PTC is significantly lower than that of healthy people, so maybe 1,25 (OH) 2 D 3 can become a potential diagnostic marker for PTC.…”
Section: Markers Related To Thyroid Functionmentioning
confidence: 99%
“…The significance of vitamin D in the diagnosis and prognosis of thyroid cancer is also conflicted, although in 2016 and 2017, Choi 25 and Danilovic 26 denied serum 25 (OH) D 3 ’s role in determining the risk of thyroid cancer in their studies respectively. But in 2018, Zhang et al found that the content of 1,25 (OH) 2 D 3 in the serum of patients with PTC is significantly lower than that of healthy people, so maybe 1,25 (OH) 2 D 3 can become a potential diagnostic marker for PTC.…”
Section: Blood Markersmentioning
confidence: 99%